Transparent electrode of deep ultraviolet LED and preparation method of transparent electrode

By forming transparent electrodes with silver/carbon nanotube/alumina composite structure on the deep ultraviolet LED epitaxial structure, the problems of insufficient brittleness and bonding strength of traditional electrode materials are solved, and the improvement of high light transmittance and conductivity is achieved, avoiding the The problem of uneven metal deposition.

CN119153603AActive Publication Date: 2024-12-17SOUTH CHINA NORMAL UNIV

Patent Information

Application Number
CN202411333947.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Traditional transparent electrode materials such as indium tin oxide have problems such as high brittleness, poor deep ultraviolet effect, insufficient bonding strength between carbon nanotubes and LED epitaxial structures, and metal deposition leads to reduced light transmittance.

Method used

Deposit silver film on the deep ultraviolet LED epitaxial structure, spin-coated carbon nanotubes and formed a silver/carbon nanotube composite structure, adding an alumina film layer, and forming a transparent electrode with a silver/carbon nanotube/alumina composite structure through rapid annealing. Improve bond strength and conductivity while maintaining light transmission.

Benefits of technology

The bonding strength and conductivity of carbon nanotubes and LED epitaxial structures are improved, the problem of uneven metal accumulation is avoided, and transparent electrodes with high light transmittance, good conductivity and mechanical strength are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153603A_ABST
    Figure CN119153603A_ABST
Patent Text Reader

Abstract

The invention relates to a transparent electrode of a deep ultraviolet LED and a preparation method of the transparent electrode. A layer of silver film is deposited on an epitaxial structure of the deep ultraviolet LED; spin-coating the silver film with the carbon nanotube suspension liquid; after drying, carrying out first-time rapid annealing in an inert atmosphere to form a silver / carbon nanotube composite structure composed of a carbon nanotube and silver nanospheres attached to the wall of the carbon nanotube; depositing an aluminum oxide film layer on the silver / carbon nanotube composite structure; and carrying out secondary rapid annealing in an inert atmosphere to form the transparent electrode with a silver / carbon nano tube / aluminum oxide composite structure, and the transparent electrode has strong bonding strength and mechanical strength and good light transmission and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optoelectronic materials, and in particular to a transparent electrode of a deep ultraviolet LED and a preparation method thereof. Background Art

[0002] As a new type of optoelectronic device, deep ultraviolet LED requires electrode materials with high transmittance and high conductivity to improve the photoelectric conversion efficiency. Traditional transparent electrode materials such as indium tin oxide (ITO) have problems such as high brittleness and poor deep ultraviolet effect, and alternative materials need to be found. Carbon nanotubes are regarded as ideal transparent electrode alternative materials due to their high transmittance, conductivity and flexibility.

[0003] However, there are also certain problems with the use of carbon nanotubes. When carbon nanotubes are used directly as transparent electrodes, there is a problem of insufficient bonding strength with the LED epitaxial structure, resulting in the loss of related properties such as conductivity; when carbon nanotubes are doped with metals or oxides to improve overall performance, chemical plating or direct deposition methods are often used to deposit metals on the surface of carbon nanotubes to form a composite structure. At this time, the surface of the carbon nanotubes is prone to metal accumulation, resulting in reduced light transmittance. At present, there is a need for a method that can strengthen the bonding strength between carbon nanotubes and deep ultraviolet LED epitaxial structures without affecting light transmittance and conductivity. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the primary purpose of the present invention is to provide a transparent electrode for deep ultraviolet LEDs and a preparation method thereof, which strengthens the bonding strength between carbon nanotubes and chips and their conductivity while ensuring transmittance and conductivity, and adds a layer of aluminum oxide film on the top layer that can ensure the bonding strength without affecting the conductivity and transmittance, thereby improving the comprehensive performance of the transparent electrode.

[0005] In one aspect, the present invention provides a method for preparing a transparent electrode of a deep ultraviolet LED, comprising the following steps:

[0006] Depositing a thin silver film on the deep ultraviolet LED epitaxial structure;

[0007] Spin coating a carbon nanotube suspension onto the silver film;

[0008] After drying, a first rapid annealing is performed in an inert atmosphere to form a silver / carbon nanotube composite structure consisting of carbon nanotubes and silver nanospheres attached to the carbon nanotube walls on the deep ultraviolet LED epitaxial structure;

[0009] Depositing an aluminum oxide film layer on the silver / carbon nanotube composite structure;

[0010] A second rapid annealing is performed in an inert atmosphere to form the transparent electrode of the silver / carbon nanotube / aluminum oxide composite structure.

[0011] Furthermore, the thickness of the silver film is 2-10 nm.

[0012] Furthermore, the carbon nanotube suspension is formed by mixing carbon nanotubes, a solvent and a surfactant and then ultrasonically treating the mixture. The surfactant is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate. The mass proportion of carbon nanotubes in the suspension is 1% to 20%. The ultrasonic time is 30 to 120 minutes.

[0013] Furthermore, in the spin coating step, the spin coating speed is 1000 to 4000 rpm, and the spin coating time is 1 to 10 minutes.

[0014] Furthermore, the thickness of the aluminum oxide film layer is 10 to 100 nm.

[0015] Furthermore, in the first annealing, annealing is performed in a nitrogen atmosphere, the annealing temperature is 300 to 700° C., and the annealing time is 30s to 120s;

[0016] In the second annealing, annealing is performed in a nitrogen atmosphere, the annealing temperature is 300-700° C., and the annealing time is 30s-120s.

[0017] On the other hand, the present invention provides a transparent electrode for a deep ultraviolet LED. The transparent electrode is arranged on a deep ultraviolet LED epitaxial structure. The transparent electrode is a silver / carbon nanotube / aluminum oxide composite structure. The silver / carbon nanotube / aluminum oxide composite structure is composed of a silver / carbon nanotube composite structure and an aluminum oxide film layer covering the silver / carbon nanotube composite structure. The silver / carbon nanotube composite structure is composed of a carbon nanotube layer and silver nanospheres attached to the carbon nanotube wall.

[0018] Furthermore, the thickness of the aluminum oxide film layer is 10 to 100 nm.

[0019] Furthermore, the particle size of the silver nanospheres is 2 to 10 nm.

[0020] Furthermore, the carbon nanotube is at least one of a single-walled carbon nanotube and a multi-walled carbon nanotube; and the carbon nanotube layer is a single layer to three layers.

[0021] The silver / carbon nanotube composite structure is obtained by thermally evaporating a silver layer on a deep ultraviolet LED epitaxial structure, then spin-coating a carbon nanotube layer on the silver layer, and finally undergoing an annealing process.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] The present invention is based on the good transmittance of carbon nanotubes and aluminum oxide to deep ultraviolet light. Silver nanoballs are arranged on the carbon nanotube walls to form a silver / carbon nanotube composite structure, which improves the bonding strength between the carbon nanotube layer and the deep ultraviolet LED epitaxial structure while ensuring light transmittance and excellent conductivity. An aluminum oxide film layer is arranged on the silver / carbon nanotube composite structure to form a transparent electrode of the silver / carbon nanotube / aluminum oxide composite structure, which protects the carbon nanotubes and further strengthens the bonding strength and mechanical strength of the transparent electrode, thereby obtaining a deep ultraviolet transparent electrode with good light transmittance and conductivity.

[0024] The present invention avoids the problem of uneven metal accumulation caused by methods such as chemical electroplating. The preparation method of the present invention deposits a silver film on a deep ultraviolet LED epitaxial structure, then spin-coats carbon nanotubes on the silver film, and utilizes the annealing ball aggregation characteristics of silver to form silver nanospheres attached to the carbon nanotube walls after rapid annealing, thereby forming a silver / carbon nanotube composite structure, thereby improving the bonding strength between the carbon nanotube layer and the deep ultraviolet LED epitaxial structure while ensuring light transmittance and excellent electrical conductivity. Further, an aluminum oxide film is deposited on the silver / carbon nanotube composite structure to form a transparent electrode of the silver / carbon nanotube / aluminum oxide composite structure, and the transparent electrode has high shape retention rate, good bonding strength and light transmittance, and excellent electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 FIG. 1 is a schematic diagram of a carbon nanotube suspension after spin coating in one embodiment of the present invention.

[0026] Figure 2 Schematic diagram of a silver / carbon nanotube / aluminum oxide composite structure obtained in one embodiment of the present invention. DETAILED DESCRIPTION

[0027] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention. The experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained from public commercial channels.

[0028] Spatially relative terms such as "below," "beneath," "below," "above," "upper," etc. are used in this specification to explain the positioning of one element relative to a second element. These terms are intended to encompass different orientations of the device in addition to different orientations than those depicted in the figures.

[0029] In addition, the use of terms such as "first", "second", etc. to describe various elements, layers, regions, sections, etc. is not intended to be limiting. The use of "having", "containing", "including", "comprising", etc. is open-ended, indicating the presence of the stated elements or features, but does not exclude additional elements or features. Unless the context clearly states otherwise.

[0030] The transparent electrode of a deep ultraviolet LED described in the present invention is formed on a deep ultraviolet LED epitaxial structure. The transparent electrode of the deep ultraviolet LED comprises: a silver / carbon nanotube composite structure formed on the deep ultraviolet LED epitaxial structure and an aluminum oxide film layer covering the silver / carbon nanotube composite structure, the thickness of the aluminum oxide film layer is 10 to 100 nm, and this thickness range ensures the ultraviolet light transmittance of the electrode; the aluminum oxide film layer is preferably deposited on the silver / carbon nanotube composite structure by a magnetron sputtering process, and other suitable deposition processes may also be used.

[0031] The silver / carbon nanotube composite structure is composed of a carbon nanotube layer and silver nanospheres attached to the carbon nanotube wall. The carbon nanotube layer is a single-layer carbon nanotube, a double-layer carbon nanotube or a triple-layer carbon nanotube, and the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube. The silver / carbon nanotube composite structure is obtained by thermally evaporating a silver layer on a deep ultraviolet LED epitaxial structure, then spin-coating a carbon nanotube layer on the silver layer, and finally undergoing an annealing process. The silver / carbon nanotube composite structure obtained by this process method avoids the problems of uneven deposition and accumulation of silver electroplated on carbon nanotubes in the traditional process. This method utilizes the annealing ball aggregation characteristics of silver to form silver nanospheres on the carbon nanotube wall, thereby improving the bonding strength between the carbon nanotube and the chip, while ensuring the light transmittance of the electrode.

[0032] The present invention also provides a method for preparing a transparent electrode of a deep ultraviolet LED, which comprises:

[0033] First, a silver film with a thickness of 2 to 10 nm is deposited on the deep ultraviolet LED epitaxial structure. The deposition process is, for example, a thermal evaporation process. In a preferred embodiment, the deposition thickness of the silver film is 5 nm, 7 nm, or 10 nm. The interior of the evaporation chamber is in a vacuum state (about 6*10 -4 Pa), and the growth rate is about 0.3nm / s.

[0034] Carbon nanotubes are configured with a solvent and a surfactant to form a suspension. The carbon nanotubes may include single-walled carbon nanotubes and multi-walled carbon nanotubes. The surfactant is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; the surfactant is added to ensure high dispersibility. The solvent is an organic solvent or an inorganic solvent, and the organic solvent is, for example, anhydrous ethanol or acetone, and the inorganic solvent is, for example, deionized water. After the carbon nanotubes, the solvent and the surfactant are mixed, an ultrasonic treatment is performed to obtain a suspension, the ultrasonic time is 30 to 120 minutes, and the mass proportion of the carbon nanotubes in the configured suspension is 1% to 20%. In a preferred embodiment, the mass proportion of the carbon nanotubes in the configured suspension is 5%, the amount of sodium dodecylbenzene sulfonate added is 0.2 g / L, and the ultrasonic time is 30 minutes to obtain a carbon nanotube suspension.

[0035] Then, the carbon nanotube suspension is spin-coated on the silver film at a spin-coating speed of 1000-4000 rpm for 1-10 minutes, and then the epitaxial structure is heated and dried. In a preferred embodiment, the carbon nanotube suspension is spin-coated on the silver film at a spin-coating speed of 2000 rpm for 2 minutes, and then placed in an oven at 65° C. for 15 minutes to obtain a dried deep ultraviolet LED epitaxial structure.

[0036] The dried deep ultraviolet LED epitaxial structure is placed in an annealing furnace and annealed in a nitrogen atmosphere. During the annealing process, the nitrogen flow rate is 0.5 L / min, the annealing temperature is 300-700°C, and the annealing time is 30s-120s. Preferably, the annealing time is 30s-90s, and a silver / carbon nanotube composite structure consisting of carbon nanotubes and silver nanospheres attached to the carbon nanotube walls is obtained on the deep ultraviolet LED epitaxial structure. In a preferred embodiment, the annealing temperature is 500°C and the annealing time is 1 min.

[0037] Next, a layer of aluminum oxide thin film with a thickness of 10 to 100 nm is deposited on the above silver / carbon nanotube composite structure. In one embodiment, a magnetron sputtering process is used to deposit the aluminum oxide thin film layer. The magnetron sputtering process can obtain a high-quality thin film with high shape retention, uniform thickness and high coverage. The sputtering thickness is controlled by controlling the sputtering time to 22 minutes, 64 minutes, and 105 minutes, and the corresponding sputtering thickness is 20 nm, 60 nm, and 100 nm.

[0038] Then, a second annealing is performed, and the epitaxial structure with the aluminum oxide film layer deposited is placed in an annealing furnace and annealed in a nitrogen atmosphere. During the annealing process, the nitrogen flow rate is 0.5 L / min, the annealing temperature is 300-700°C, and the annealing time is 30s-120s. Preferably, the annealing time is 30s-90s, and a silver / carbon nanotube composite structure composed of carbon nanotubes and silver nanospheres attached to the carbon nanotube wall formed on the deep ultraviolet LED epitaxial structure is obtained. In a preferred embodiment, the annealing temperature is 400°C, 500°C, 600°C, and the annealing time is 1 min.

[0039] The above preparation method finally obtained a silver / carbon nanotube / aluminum oxide transparent electrode with good light transmittance, improved conductivity and good bonding strength.

[0040] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a transparent electrode for a deep ultraviolet LED, characterized in that: The steps include: Depositing a thin silver film on the deep ultraviolet LED epitaxial structure; Spin coating a carbon nanotube suspension onto the silver film; After drying, a first rapid annealing is performed in an inert atmosphere to form a silver / carbon nanotube composite structure consisting of carbon nanotubes and silver nanospheres attached to the carbon nanotube walls on the deep ultraviolet LED epitaxial structure; Depositing an aluminum oxide film layer on the silver / carbon nanotube composite structure; A second rapid annealing is performed in an inert atmosphere to form the transparent electrode of the silver / carbon nanotube / aluminum oxide composite structure.

2. The preparation method according to claim 1, characterized in that: The thickness of the silver film is 2-10 nm.

3. The preparation method according to claim 1 or 2, characterized in that: The carbon nanotube suspension is prepared by mixing carbon nanotubes, a solvent and a surfactant and then ultrasonicating the mixture. The surfactant is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate. The mass proportion of carbon nanotubes in the suspension is 1% to 20%. The ultrasonication time is 30 to 120 minutes.

4. The preparation method according to claim 3, characterized in that: In the spin coating step, the spin coating speed is 1000-4000 rpm, and the spin coating time is 1-10 min.

5. The preparation method according to claim 1, 2 or 4, characterized in that: The thickness of the aluminum oxide film layer is 10-100 nm.

6. The preparation method according to claim 5, characterized in that: In the first annealing, annealing is performed in a nitrogen atmosphere, the annealing temperature is 300 to 700° C., and the annealing time is 30s to 120s; In the second annealing, annealing is performed in a nitrogen atmosphere, the annealing temperature is 300-700° C., and the annealing time is 30s-120s.

7. A transparent electrode of a deep ultraviolet LED, wherein the transparent electrode is arranged on a deep ultraviolet LED epitaxial structure, characterized in that: The transparent electrode is a silver / carbon nanotube / aluminum oxide composite structure, which is composed of a silver / carbon nanotube composite structure and an aluminum oxide film layer covering the silver / carbon nanotube composite structure, and the silver / carbon nanotube composite structure is composed of a carbon nanotube layer and silver nanospheres attached to the carbon nanotube wall.

8. The transparent electrode according to claim 7, characterized in that: The thickness of the aluminum oxide film layer is 10-100 nm.

9. The transparent electrode according to claim 7 or 8, characterized in that: The particle size of the silver nanospheres is 2-10 nm.

10. The transparent electrode according to claim 9, characterized in that: The carbon nanotubes are at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; and the carbon nanotube layer is a single layer to three layers.

Citation Information

Patent Citations

  • Carbon nanotube / silver nanowire composite film, gallium arsenide-based heterojunction solar cell thereof and preparation method of gallium arsenide-based heterojunction solar cell

    CN114823931A

  • Electrode-interface layer composite structure with contacted network-shaped bodies, and preparation method and application of electrode-interface layer composite structure

    CN116801691A

  • Carbon nano-tube(CNT) thin film comprising a metal nano-particle, and a manufacturing method thereof

    KR1020080112799A

  • Automated method of measuring ship's underwater radiated noise using GPS

    KR1020240077925A

Cited By

  • A method for manufacturing a high-conductivity transparent electrode based on a short-time broadband electromagnetic field

    CN122762390A